(20S *,24S *)-25-Hydroxy-20,24-epoxy-A-homo-4-oxadammaran-3-one (Chrysura) isolated from the leaves of Walsura chrysogyne. - Mahmod, Ilya Iryani; Huey, Chong Kwong; Mohamed Tahir, Mohamed Ibrahim; Ismail, Intan Safinar (International Union of Crystallography, 2011)
The title dammarane triterpenoid, C30H50O4, assigned the name chrysura, was isolated from an ethyl acetate extract of Walsura chrysogyne leaves (Meliaceae). It has 20S*,24S* relative stereochemistry and an oxepanone ring with two methyl groups at position 4. The two cyclohexane rings adopt chair conformations. The cyclopentane and tetrahydrofuran rings have envelope conformations; their mean planes make a dihedral angle of 13.1 (3)°, indicating that the rings are only slightly tilted with respect to each other. There is an intramolecular C—H(...)O hydrogen bond in the molecule, which forms S(6) and S(7) ring motifs. In the crystal, molecules are linked via O—H(...)O and C—H(...)O hydrogen bonds, forming chains propagating along [001] which stack along the b-axis direction.